UNISCIJ 2020
DOI: 10.31439/unisci-86
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Women Contribution in Peace, Conflict Resolution, and Security Agenda: Indonesian Female Peacekeepers in the United Nations Peacekeeping Operation (Garuda Contingent – KONGA)

Abstract: Many scholars have argued that security, peace and conflict are gender neutral. However, studies have shown that women and men experience conflict differently. This article analyses the need to increase women's role in peace and conflict resolution agenda, particularly based on the experience of the Indonesian Female Peacekeepers in the United Nations Peacekeeping Operation. Feminist theoretical framework and gender analysis were used to look at the impact experienced by men and women during wartime, and women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The same thing also happened in Indonesia. Socio-cultural problems are caused by a military culture that is hypermasculine and strong stereotypes that prevent women from working in the security sector, including as peacekeepers (Azizah, Maksum, & Hidayahtulloh, 2020). The involvement of women is also said to be constrained by traditional reluctance from the family, thus limiting women's opportunities to contribute (Dewi, Satya, & Arsanti, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The same thing also happened in Indonesia. Socio-cultural problems are caused by a military culture that is hypermasculine and strong stereotypes that prevent women from working in the security sector, including as peacekeepers (Azizah, Maksum, & Hidayahtulloh, 2020). The involvement of women is also said to be constrained by traditional reluctance from the family, thus limiting women's opportunities to contribute (Dewi, Satya, & Arsanti, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Nur Azizah, Ali Maksum, and Muhammad Ammar Hidayatulloh wrote a journal entitled Enhacing Women Contribution in Peace, Conflict Resolution and Security Agenda: Indonesia Female Peacekeepers in the United Nationa Peacekeeping Operations (Garuda Contingent Konga).The analysis of this paper is that this article explains the importance of increasing the role of women which is in the peace agenda and conflict resolution agenda, especially based on the experience of the Indonesian Women's Peacekeepers in Peacekeeping Operations at the United Nations. It is also said that changes in the characteristics of war from an interstate conflict and at this time require a human security framework and require peacekeeping capabilities which are in order to be able to move closer to the people (Azizah, Maksum, & Hidayahtulloh, 2020) inHumanitarian Assistancein Lebanon. The author analyzes this paper which is intended to recognize the role of women in the TNI who are members of the Garuda troops where they are sent to Lebanon using the concept of peace and also humanitarian assistance (Firohmatillah & Sudirman, 2019).…”
Section: Rany Purnama Hadi and Sartika Soesilowati Through Their Writ...mentioning
confidence: 99%
“…The Indonesian government, under the President Joko Widodo's administration, has declared the Indonesian Roadmap Vision for 4000 Peacekeepers (2015-2019) (Azizah, Maksum, & Hidayahtulloh, 2020). The Minister of Foreign Affairs Retno Marsudi announced that this roadmap also includes Indonesia's commitment to implement the WPS Agenda by increasing the number of Indonesian female peacekeepers in UN PKO .…”
Section: The Wps Agenda In Indonesia's Foreign Policymentioning
confidence: 99%
“…Women and men experience the impact of armed conflicts differently as women and girls have been predominantly subjected to sexual violence and rape (Chinkin, 1994;Hynes, 2004). Considering pervasive gender-based violence in the areas of conflicts, other scholars suggested that women's participation in conflict resolution and peace processes through a global institution such as UN Peacekeeping Operations (UN PKO) was critical to maintain international peace and security (Dharmapuri, 2011;Szymanski, 2016;Azizah, Maksum, & Hidayahtulloh, 2020). Therefore, the United Nations Security Council (UNSC) adopted Resolution 1325 on Women, Peace, and Security (hereinafter: WPS Agenda) in 2000.…”
Section: Introductionmentioning
confidence: 99%